1997
DOI: 10.1590/s0103-50531997000200013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature and pH on the dissolution and passivation processes of copper in carbonate-bicarbonate solutions

Abstract: Foram feitos estudos eletroquímicos de eletrodos de cobre policristalino em soluções de carbonato-bicarbonato, analisando os efeitos da temperatura e do pH, cobrindo uma extensa faixa de composições eletrolíticas num intervalo de 5-65 °C. As condições hidrodinâmicas do sistema também foram consideradas. Os resultados são explicados com base numa modificação das características do filme decorrente dos efeitos de agitação da solução e das temperaturas elevadas. Nestas situações, forma-se uma camada menos hidrata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Kaluzhina and Sieber 29 made similar observations in their voltammograms of copper in 0.02 M/ 0.1 M bicarbonate solutions at slow sweep rates (10 mV s −1 ) but not at fast sweep rates (100 mV s −1 ). Both Ribotta and Folquer 30 and Kaluzhina and Sieber 29 state that the second oxidation peak relates to the formation of CuCO 3 .Cu(OH) 2 , in accordance with the Pourbaix diagram. Kaluzhina and Sieber 29 propose that the behavior observed at lower sweep rates is due to the concurrent formation of a very thin layer of CuO with the CuCO 3 .Cu(OH) 2 initially, that goes on to dissolve when in contact with the electrolyte.…”
Section: Resultssupporting
confidence: 55%
“…Kaluzhina and Sieber 29 made similar observations in their voltammograms of copper in 0.02 M/ 0.1 M bicarbonate solutions at slow sweep rates (10 mV s −1 ) but not at fast sweep rates (100 mV s −1 ). Both Ribotta and Folquer 30 and Kaluzhina and Sieber 29 state that the second oxidation peak relates to the formation of CuCO 3 .Cu(OH) 2 , in accordance with the Pourbaix diagram. Kaluzhina and Sieber 29 propose that the behavior observed at lower sweep rates is due to the concurrent formation of a very thin layer of CuO with the CuCO 3 .Cu(OH) 2 initially, that goes on to dissolve when in contact with the electrolyte.…”
Section: Resultssupporting
confidence: 55%
“…SEM examination as shown in Figure c further confirmed that the passive film was more compact. Ribotta et al confirmed this view in cycle voltammetry where the sharp and symmetrical reduction current peaks at higher temperature indicated that the film was more compact and adhesive.…”
Section: Discussionmentioning
confidence: 81%
“…It is important to note that carbonate and bicarbonate solutions were extensively studied as electrolytes for corrosion studies of copper in the '90s and early '00s using cyclic voltammetry and rotating disk electrode [25][26][27][28][29]. Carbonates are usually present in the waterespecially in hard waterand can have an impact on the corrosion protection of copper pipes caused by other anions [26].…”
Section: Introductionmentioning
confidence: 99%
“…Carbonates are usually present in the waterespecially in hard waterand can have an impact on the corrosion protection of copper pipes caused by other anions [26]. It was recognized that bicarbonate ions prevent copper corrosion [30], and the electrochemical response of copper depends on temperature, pH, ionic strength of the electrolyte, and hydrodynamic conditions (i.e., stirring) [25]. Similarly to anodizing in highly alkaline solutions, the passive layer obtained in carbonates is duplex in nature.…”
Section: Introductionmentioning
confidence: 99%